Modified carbon nanotubes, preparation thereof, and easily dispersible storage-stable carbon nanotube conductive paste containing the same and method of preparing the same
Patent Information
- Application Number
- CN202410271757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-03-11
AI Technical Summary
然而这些技术制备的导电浆料中碳纳米管的浓度相对较低,以管径为5-10nm的碳纳米管为例,浆料中的碳纳米管含量一般不超过5wt%,这增加了导电浆料的生产、运输和储存成本
[0035] This invention addresses the shortcomings of existing technologies by providing a method for preparing modified carbon nanotubes. The method utilizes a modifier to successfully graft sulfonic acid groups and/or carboxyl groups from the modifier's molecular structure onto carbon nanotubes. The modification process does not involve concentrated acid treatment, offering advantages such as simple reaction procedures, mild reaction conditions, and environmental friendliness. The resulting modified carbon nanotubes exhibit excellent dispersion stability in solvents. Furthermore, the modified carbon nanotubes are introduced into the preparation of carbon nanotube conductive slurries. Through the abundant sulfonic acid groups and/or carboxyl groups on the modified carbon nanotubes, the resulting conductive slurry possesses advantages such as high carbon nanotube concentration, good dispersibility, good flowability, and non-settling, non-stratification, and non-thickening properties during storage. It is suitable for use as a positive and negative electrode slurry in lithium-ion secondary batteries.
Smart Images

Figure BDA0004734501340000081 
Figure BDA0004734501340000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of conductive paste preparation technology, specifically including modified carbon nanotubes, their preparation, and easily dispersible, storage-stable carbon nanotube conductive pastes containing them, as well as their preparation methods. Background Technology
[0002] Driven by increasingly stringent global environmental policies, new energy vehicles are developing rapidly. As a key component of new energy vehicles, power lithium batteries are evolving towards higher energy density and longer cycle life. High-nickel cathodes and silicon-carbon anodes represent future trends, but these electrode materials generally suffer from poor conductivity, preventing the full utilization of the electrode's effective energy. To improve electrode conductivity, conductive carbon black is typically added as a conductive agent. However, because carbon black and active materials have point-to-point contact, electron transport efficiency is limited, often requiring a high addition amount. This reduces the lithium battery's capacity, failing to meet the demands for high energy density.
[0003] Carbon nanotubes possess a high aspect ratio and exhibit point-to-line contact with active materials, effectively forming a three-dimensional conductive structure with a conductivity 3-5 times higher than that of conductive carbon black. This allows for electrode conductivity to be maintained with relatively small addition amounts. However, due to the linear structure and strong van der Waals attraction between molecules, carbon nanotubes are prone to aggregation and entanglement, resulting in poor dispersibility and affecting their conductivity. Furthermore, the prepared carbon nanotube conductive slurry is prone to thickening during storage, leading to decreased flowability and reduced usability for end users. Existing technologies generally employ high-performance dispersants to improve the dispersibility and stability of carbon nanotube conductive slurries. For example, CN108059151A discloses a polymer of polyethylene glycol and acrylonitrile as a carbon nanotube dispersant, achieving high dispersion efficiency and significantly reducing dispersion costs; CN116873903A discloses a method for dispersing carbon nanotubes using hydrogenated nitrile butadiene rubber and anhydrous piperazine as dispersants, resulting in a conductive slurry with good dispersibility and stability. However, the concentration of carbon nanotubes in the conductive pastes prepared by these technologies is relatively low. Taking carbon nanotubes with a diameter of 5-10 nm as an example, the carbon nanotube content in the paste is generally no more than 5 wt%, which increases the production, transportation, and storage costs of the conductive paste. Furthermore, relying solely on the physical adsorption between the dispersant and the carbon nanotubes is insufficient to guarantee the long-term storage stability of the paste. Therefore, it is necessary to develop a carbon nanotube conductive paste that is easily dispersible and stable in storage, while also possessing the advantages of high carbon nanotube concentration and good storage stability, in order to solve the problems existing in the current technologies. Summary of the Invention
[0004] In view of the above-mentioned problems in the prior art, the first objective of the present invention is to provide a method for preparing modified carbon nanotubes.
[0005] A second object of the present invention is to provide modified carbon nanotubes prepared by the preparation method described above.
[0006] A third objective of this invention is to provide a carbon nanotube conductive paste containing the modified carbon nanotubes as described above, which is easily dispersed and has stable storage properties.
[0007] The fourth objective of this invention is to provide a method for preparing the easily dispersible, storage-stable, and conductive carbon nanotube slurry as described above.
[0008] To achieve the first objective mentioned above, the technical solution adopted by this invention includes:
[0009] This invention discloses a method for preparing modified carbon nanotubes, wherein the modified carbon nanotubes are carbon nanotubes with carboxylic acid or sulfonic acid functional groups on their surface after surface modification. The preparation method is as follows:
[0010] Carbon nanotube powder, modifier and water are mixed to obtain carbon nanotube mixture A;
[0011] Heating to 65-75℃ and adding an aqueous solution of sodium nitrite yields carbon nanotube mixture B;
[0012] Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, stir at 65-75℃ for 1-2 hours, filter, wash with hot water at 50-60℃ until the pH of the filtrate is 7-8, and collect the filtrate to obtain the final product.
[0013] The modifier contains at least the following three types of functional groups in its molecular structure: 1) primary amino group; 2) phenyl and / or naphthyl group; 3) sulfonic acid group and / or carboxyl group.
[0014] Furthermore, the mass ratio of the carbon nanotube powder, modifier, and water is 10:0.5-4:150-250; preferably 10:1-3:200.
[0015] Furthermore, the modifier is selected from one or more of 4-amino-1-naphthalenesulfonic acid, 4-amino-1-naphthoic acid, 5-amino-1-naphthalenesulfonic acid, 5-amino-1-naphthoic acid, p-aminobenzoic acid, p-aminobenzenesulfonic acid, m-aminobenzoic acid, and m-aminobenzenesulfonic acid.
[0016] The carbon nanotube powder is selected from one or more of single-walled carbon nanotubes, oligo-walled carbon nanotubes, and multi-walled carbon nanotubes, with an average diameter ranging from 2 to 80 nm; preferably 5 to 30 nm.
[0017] Furthermore, the mass ratio of the carbon nanotube powder to the sodium nitrite aqueous solution is 10:30-50; the concentration of the sodium nitrite aqueous solution is 2-3 wt%.
[0018] To achieve the second objective mentioned above, the technical solution adopted by the present invention includes:
[0019] This invention discloses a modified carbon nanotube prepared using the preparation method described above.
[0020] To achieve the third objective mentioned above, the technical solution adopted by this invention includes:
[0021] This invention discloses a carbon nanotube conductive paste comprising the modified carbon nanotubes as described above, which, by mass percentage, comprises the following raw materials:
[0022] Modified carbon nanotubes 0.5-15 wt%;
[0023] Dispersant 0.1-15wt%;
[0024] The remainder is solvent.
[0025] Furthermore, the dispersant is selected from one or more of the following: styrene / acrylic acid copolymer, polyurethane polymer, polyester polymer, butadiene / acrylic acid copolymer, styrene / maleic acid copolymer, polyethylene glycol monovinyl ether / maleic acid copolymer, polyacrylate or its modified polymer, epoxy polyether amine addition polymer, polyvinylpyrrolidone or its modified polymer.
[0026] Furthermore, the solvent is selected from one or more of water, N-methylpyrrolidone, propylene glycol methyl ether acetate, butyl acetate, and methyl isobutyl ketone.
[0027] Furthermore, the carbon nanotube conductive paste contains 6-12 wt% modified carbon nanotubes.
[0028] To achieve the fourth objective mentioned above, the technical solution adopted by this invention includes:
[0029] This invention discloses a method for preparing the carbon nanotube conductive paste as described above, comprising the following steps:
[0030] (1) Add the dispersant to the solvent according to the formula amount, and stir at a speed of 800-1000 r / min for 10-20 min to obtain mixture A;
[0031] (2) Add modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0032] (3) Grind mixture B in sand, keeping it in a grinding state until the fineness of the material is dispersed to <20μm, to obtain mixture C;
[0033] (4) The mixture C is subjected to high-pressure homogenization dispersion treatment to obtain the carbon nanotube conductive slurry.
[0034] Beneficial effects of this invention:
[0035] This invention addresses the shortcomings of existing technologies by providing a method for preparing modified carbon nanotubes. The method utilizes a modifier to successfully graft sulfonic acid groups and / or carboxyl groups from the modifier's molecular structure onto carbon nanotubes. The modification process does not involve concentrated acid treatment, offering advantages such as simple reaction procedures, mild reaction conditions, and environmental friendliness. The resulting modified carbon nanotubes exhibit excellent dispersion stability in solvents. Furthermore, the modified carbon nanotubes are introduced into the preparation of carbon nanotube conductive slurries. Through the abundant sulfonic acid groups and / or carboxyl groups on the modified carbon nanotubes, the resulting conductive slurry possesses advantages such as high carbon nanotube concentration, good dispersibility, good flowability, and non-settling, non-stratification, and non-thickening properties during storage. It is suitable for use as a positive and negative electrode slurry in lithium-ion secondary batteries. Detailed Implementation
[0036] To more clearly illustrate the present invention, specific embodiments are described below. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive and should not be construed as limiting the scope of protection of the present invention. Unless otherwise stated, all parts and percentages mentioned in the specific embodiments are by weight, all percentages are by weight, and all raw materials used are commercially available.
[0037] Modified carbon nanotubes
[0038] Currently, most commercially available carbon nanotubes are produced by chemical vapor deposition (CVD), resulting in powders that are often fibrous aggregates and entanglements. Although their surfaces may contain some modified groups (such as hydroxyl and carboxyl groups), their dispersion stability remains relatively poor. Furthermore, the carbon atoms in carbon nanotubes are sp. 2 The hybridization and extremely strong intermolecular forces make it difficult to disperse carbon nanotubes and prepare them into conductive pastes.
[0039] The carbon nanotube powder used in this invention was purchased from Shandong Dazhan Nanomaterials Co., Ltd. or Zhejiang Carbon Peak New Material Technology Co., Ltd.
[0040] Regarding the dispersibility of carbon nanotubes, one improvement approach is to reduce the particle size or arrangement of carbon nanotubes through physical means to lower the viscosity threshold during dispersion. For example, CN206011683U discloses a method for pre-treating carbon nanotubes using a high-efficiency twin-screw extruder, which improves dispersibility by reducing the agglomeration particle size of carbon nanotubes. CN113562725A discloses a method that improves the dispersibility of carbon nanotubes by pre-mixing, rolling, and extruding carbon nanotube powder, causing the powder to evolve from an agglomerated and disordered state into a smooth and ordered state. However, physical methods generally involve complex processes, high energy consumption, and low efficiency. Another method to improve the dispersibility of carbon nanotubes is through chemical modification, altering the chemical functional groups on the surface of carbon nanotubes. For example, patent CN115831442A discloses a method for modifying carbon nanotubes using concentrated sulfuric acid and potassium permanganate. However, this method consumes a large amount of acid, causes significant secondary pollution, and is difficult to treat waste liquid, making it uneconomical and environmentally unfriendly.
[0041] This invention utilizes a chemical grafting surface treatment method to graft carboxylic acid or sulfonic acid functional groups onto carbon nanotubes through chemical modification. This reaction does not involve concentrated acid treatment and has advantages such as simple reaction process, mild reaction conditions, and environmental friendliness. Carboxylic acid or sulfonic acid functional groups can effectively improve the dispersibility and stability of modified carbon nanotubes in solvents, which is beneficial for further preparing conductive pastes with high carbon nanotube concentration, good dispersibility, good flowability, and no sedimentation, stratification, or thickening during storage.
[0042] This invention provides a modified carbon nanotube, the preparation steps of which are as follows:
[0043] Carbon nanotube powder, modifier and water are mixed to obtain carbon nanotube mixture A;
[0044] Heating to 65-75℃ and adding an aqueous solution of sodium nitrite yields carbon nanotube mixture B;
[0045] Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, stir at 65-75℃ for 1-2 hours, filter, wash with hot water at 50-60℃ until the pH of the filtrate is 7-8, and collect the filtrate to obtain the final product.
[0046] The modifier contains at least the following three types of functional groups in its molecular structure: 1) primary amino group; 2) phenyl and / or naphthyl group; 3) sulfonic acid group and / or carboxyl group.
[0047] Modifiers containing primary amine, phenyl, and / or naphthyl groups can more easily graft sulfonic acid and / or carboxyl groups onto carbon nanotubes. Experiments have shown that if the modifier does not contain phenyl and / or naphthyl groups, it is not easy to graft sulfonic acid and / or carboxyl groups onto carbon nanotubes during modification, affecting the modification efficiency of carbon nanotubes. For this invention, only when a relatively abundant number of sulfonic acid and / or carboxyl groups are introduced onto the surface of carbon nanotubes can the dispersibility and stability of modified carbon nanotubes in solvents be effectively improved, thereby obtaining an easily dispersible and storage-stable conductive carbon nanotube slurry.
[0048] Furthermore, the mass ratio of the carbon nanotube powder, modifier, and water is 10:0.5-4:150-250. For example, the mass ratio of the carbon nanotube powder, modifier, and water can also be 10:1-3:150-250, 10:1-3:150-200, 10:1-3:200-250, 10:0.5-4:150-200, 10:0.5-4:200-250, 10:2-2.5:150-250, 10:2-2.5:200-250, 10:2-2.5:150-200, etc. When the mass ratio of the carbon nanotube powder, modifier, and water is 10:1-3:200, it is more advantageous for the subsequent preparation of easily dispersed, stored, and stable carbon nanotube conductive paste.
[0049] Furthermore, the carbon nanotube powder is a commercially available product and can be one or more of single-walled carbon nanotubes, oligo-walled carbon nanotubes, and multi-walled carbon nanotubes, with an average diameter ranging from 2 to 80 nm.
[0050] Furthermore, the modifier is selected from one or more of 4-amino-1-naphthalenesulfonic acid, 4-amino-1-naphthoic acid, 5-amino-1-naphthalenesulfonic acid, 5-amino-1-naphthoic acid, p-aminobenzoic acid, p-aminobenzenesulfonic acid, m-aminobenzoic acid, and m-aminobenzenesulfonic acid. The modification effects of the above modifiers are quite similar. From a cost perspective, p-aminobenzoic acid and p-aminobenzenesulfonic acid, which have lower costs, are preferred.
[0051] Furthermore, the mass ratio of the carbon nanotube powder to the sodium nitrite aqueous solution is 10:30-50; the concentration of the sodium nitrite aqueous solution is 2-3 wt%; preferably 2.5 wt%.
[0052] Carbon nanotube conductive paste
[0053] Currently, there are many reports on conductive pastes containing large-diameter (above 40 nm) carbon nanotubes in the research of carbon nanotube conductive pastes, and the concentration of carbon nanotubes in the conductive pastes can reach more than 10 wt%. However, there are still relatively few conductive pastes containing high concentrations of small-diameter (below 30 nm) carbon nanotubes. Based on this, the present invention provides a conductive paste containing the modified carbon nanotubes as described above. By introducing carbon nanotubes modified with carboxylic acid or sulfonic acid functional groups, a carbon nanotube conductive paste with high carbon nanotube concentration and stable storage can be obtained.
[0054] In a preferred embodiment of the present invention, the modified carbon nanotubes in the easily dispersed, stable carbon nanotube conductive slurry have a mass percentage content of 0.5-15 wt%, preferably 6-12 wt%, and the specific value is determined according to the diameter of the carbon nanotube powder. When the average diameter of the carbon nanotube powder used to produce the modified carbon nanotubes is 5-10 nm (excluding 10 nm), the mass percentage of the modified carbon nanotubes in the easily dispersible, storage-stable carbon nanotube conductive slurry can be 0.5-10 wt%, preferably 5-7 wt%, and exemplaryly, it can be 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, etc.; when the average diameter of the carbon nanotube powder used to produce the modified carbon nanotubes is 10-20 nm (excluding 20 nm), the mass percentage of the modified carbon nanotubes in the easily dispersible, storage-stable carbon nanotube conductive slurry can be 6-10 wt%, preferably 8-10 wt%, and exemplaryly, it can be 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, etc. When the average diameter of the carbon nanotube powder used to produce the modified carbon nanotubes is 20-30 nm, the mass percentage of the modified carbon nanotubes in the easily dispersed, stable carbon nanotube conductive slurry can be 8-13 wt%, preferably 10-13 wt%, and exemplary, it can be 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, etc.
[0055] In a preferred embodiment of the present invention, the raw materials of the carbon nanotube conductive paste further include a dispersant, which is selected from one or more of the following: styrene / acrylic acid copolymer, polyurethane polymer, polyester polymer, butadiene / acrylic acid copolymer, styrene / maleic acid copolymer, polyethylene glycol monovinyl ether / maleic acid copolymer, polyacrylate or its modified polymer, epoxy polyetheramine addition polymer, polyvinylpyrrolidone or its modified polymer. Examples include: CLARIANT's Dispersogen PL30, BYK's DISPERBYK-2013, BYK's DISPERBYK-2014, BASF's K30, BASF's EFKA-4310, and Yuka Chemicals' UNIQ SPERSE 580U.
[0056] In a preferred embodiment of the present invention, the dispersant in the easily dispersible and stable carbon nanotube conductive slurry contains 0.1-15 wt% by mass, the specific value being determined according to the diameter of the carbon nanotube powder. When the average diameter of the carbon nanotube powder used to produce the modified carbon nanotubes is 5-10 nm (excluding 10 nm), the dispersant in the easily dispersible and stable carbon nanotube conductive slurry can be 0.1-10 wt%, preferably 1-3 wt%, and exemplary values can be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, 2.1 wt%, 2.2 wt%, etc. The dispersant can be 2-10 wt%, preferably 2-6 wt%, and for example, 2 wt%, 3 wt%, etc., when the average diameter of the carbon nanotube powder used to produce the modified carbon nanotubes is 10-20 nm (excluding 20 nm), the mass percentage of the dispersant in the easily dispersible, storage-stable carbon nanotube conductive slurry can be 2-15 wt%, preferably 3-8 wt%, and for example, 3 wt%, 4 wt%, 5 wt%, 6 wt%, etc.
[0057] In a preferred embodiment of the present invention, in addition to the modified carbon nanotubes and the dispersant, the other raw material components of the easily dispersed and stable carbon nanotube conductive slurry are solvents, and the solvents are selected from one or more of water, N-methylpyrrolidone, propylene glycol methyl ether acetate, butyl acetate, and methyl isobutyl ketone.
[0058] The present invention also provides a method for preparing the carbon nanotube conductive paste as described above, comprising the following steps:
[0059] (1) Add the dispersant to the solvent according to the formula amount, and stir at a speed of 800-1000 r / min for 10-20 min to obtain mixture A;
[0060] (2) Add modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0061] (3) Grind mixture B in sand, keeping it in a grinding state until the fineness of the material is dispersed to <20μm, to obtain mixture C;
[0062] (4) The mixture C is subjected to high-pressure homogenization dispersion treatment to obtain the carbon nanotube conductive slurry.
[0063] Furthermore, the grinding media used during sanding are 0.6-0.8mm zirconium beads.
[0064] Furthermore, the dispersion pressure in step (4) is 600-800 bar.
[0065] The equipment used in this preparation method is all general-purpose equipment found in conductive paste production plants, which is suitable for large-scale industrial production and has good practicality.
[0066] Example 1
[0067] A method for preparing an aqueous, easily dispersible, and storage-stable conductive carbon nanotube slurry includes the following steps:
[0068] S1. Modified carbon nanotubes
[0069] S1.1 Mix 10 parts of carbon nanotube powder with an average tube diameter of 5-10 nm and an average tube length of 30 μm with 2 parts of modifier 4-amino-1-naphthoic acid and 200 parts of water to obtain carbon nanotube mixture A; heat to 65-75℃ in a water bath under mechanical stirring.
[0070] S1.2 Add 35 parts of a 2.5 wt% sodium nitrite aqueous solution to carbon nanotube mixture A to obtain carbon nanotube mixture B;
[0071] S1.3 Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, and stir rapidly at 65-75℃ for 1 hour to obtain carbon nanotube mixture C;
[0072] S1.4 Filter the carbon nanotube mixture C and wash it with hot water at 50-60℃ until the pH of the filtrate is 7-8. Collect the filtrate and dry it at 70℃ to obtain modified carbon nanotubes.
[0073] S2. Preparation of carbon nanotube conductive paste
[0074] S2.1 Add 2 parts of dispersant Dispersogen PL30 to 92 parts of water and stir at 800-1000 r / min for 10 min to obtain mixture A;
[0075] S2.2 Add 6 parts of the above modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0076] S2.3 The mixture B is sand-milled with 0.6-0.8 mm zirconium beads as the grinding media, and the grinding is maintained until the fineness of the material is dispersed to <20 μm to obtain mixture C;
[0077] S2.4 The mixture C is subjected to high-pressure homogenization dispersion treatment at a dispersion pressure of 600-800 bar to obtain the water-based, easily dispersible, and storage-stable carbon nanotube conductive slurry.
[0078] Example 2
[0079] A method for preparing an aqueous, easily dispersible, and storage-stable conductive carbon nanotube slurry includes the following steps:
[0080] S1. Modified carbon nanotubes
[0081] S1.1 Mix 10 parts of carbon nanotube powder with an average tube diameter of 20-30 nm and an average tube length of 50 μm with 2.5 parts of modifier 4-amino-1-naphthoic acid and 200 parts of water to obtain carbon nanotube mixture A; heat to 65-75℃ in a water bath under mechanical stirring.
[0082] S1.2 Add 45 parts of a 2.5 wt% sodium nitrite aqueous solution to carbon nanotube mixture A to obtain carbon nanotube mixture B;
[0083] S1.3 Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, and stir rapidly at 65-75℃ for 1 hour to obtain carbon nanotube mixture C;
[0084] S1.4 Filter the carbon nanotube mixture C and wash it with hot water at 50-60℃ until the pH of the filtrate is 7-8. Dry it at 70℃ to obtain modified carbon nanotubes.
[0085] S2. Preparation of carbon nanotube conductive paste
[0086] S2.1 Add 4 parts of dispersant K30 to 84 parts of water and stir at 800-1000 r / min for 10 min to obtain mixture A;
[0087] S2.2 Add 12 parts of the above modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0088] S2.3 The mixture B is sand-milled with 0.6-0.8 mm zirconium beads as the grinding media, and the grinding is maintained until the fineness of the material is dispersed to <20 μm to obtain mixture C;
[0089] S2.4 The mixture C is subjected to high-pressure homogenization dispersion treatment at a dispersion pressure of 600-800 bar to obtain the water-based, easily dispersible, and storage-stable carbon nanotube conductive slurry.
[0090] Example 3:
[0091] A method for preparing an oil-based, easily dispersible, and storage-stable conductive carbon nanotube slurry includes the following steps:
[0092] S1. Modified carbon nanotubes
[0093] S1.1 Mix 10 parts of carbon nanotube powder with an average tube diameter of 5-10 nm and an average tube length of 30 μm with 2 parts of modifier 4-amino-1-naphthoic acid and 200 parts of water to obtain carbon nanotube mixture A; heat to 65-75℃ in a water bath under mechanical stirring.
[0094] S1.2 Add 35 parts of a 2.5 wt% sodium nitrite aqueous solution to carbon nanotube mixture A to obtain carbon nanotube mixture B;
[0095] S1.3 Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, and stir rapidly at 65-75℃ for 1 hour to obtain carbon nanotube mixture C;
[0096] S1.4 Filter the carbon nanotube mixture C and wash it with hot water at 50-60℃ until the pH of the filtrate is 7-8. Dry it at 70℃ to obtain modified carbon nanotubes.
[0097] S2. Preparation of carbon nanotube conductive paste
[0098] S2.1 Add 2.5 parts of dispersant DISPERBYK-2013 to 92 parts of NMP and stir at 800-1000 r / min for 10 min to obtain mixture A;
[0099] S2.2 Add 5.5 parts of the above modified carbon nanotubes to mixture A and disperse at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0100] S2.3 The mixture B is sand-milled with 0.6-0.8 mm zirconium beads as the grinding media, and the grinding is maintained until the fineness of the material is dispersed to <20 μm to obtain mixture C;
[0101] S2.4 The mixture C is subjected to high-pressure homogenization dispersion treatment at a dispersion pressure of 600-800 bar to obtain the oily, easily dispersible, and stable carbon nanotube conductive slurry.
[0102] Example 4
[0103] A method for preparing an oil-based, easily dispersible, and storage-stable conductive carbon nanotube slurry includes the following steps:
[0104] S1. Modified carbon nanotubes
[0105] S1.1 Mix 10 parts of carbon nanotube powder with an average tube diameter of 20-30 nm and an average tube length of 50 μm with 2.5 parts of modifier 4-amino-1-naphthalenesulfonic acid and 200 parts of water to obtain carbon nanotube mixture A; heat to 65-75℃ in a water bath under mechanical stirring.
[0106] S1.2 Add 45 parts of a 2.5 wt% sodium nitrite aqueous solution to carbon nanotube mixture A to obtain carbon nanotube mixture B;
[0107] S1.3 Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, and stir rapidly at 65-75℃ for 1 hour to obtain carbon nanotube mixture C;
[0108] S1.4 Filter the carbon nanotube mixture C and wash it with hot water at 50-60℃ until the pH of the filtrate is 7-8. Dry it at 70℃ to obtain modified carbon nanotubes.
[0109] S2. Preparation of carbon nanotube conductive paste
[0110] S2.1 Add 3 parts of dispersant EFKA-4310 to 87 parts of NMP and stir at 800-1000 r / min for 10 min to obtain mixture A;
[0111] S2.2 Add 10 parts of the above modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B;
[0112] S2.3 The mixture B is sand-milled with 0.6-0.8 mm zirconium beads as the grinding media, and the grinding is maintained until the fineness of the material is dispersed to <20 μm to obtain mixture C;
[0113] S2.4 The mixture C is subjected to high-pressure homogenization dispersion treatment at a dispersion pressure of 600-800 bar to obtain the oily, easily dispersible, and stable carbon nanotube conductive slurry.
[0114] Comparative Example 1
[0115] Example 1 was repeated, except that the two parts of the modifier 4-amino-1-naphthoic acid used in the preparation of modified carbon nanotubes were replaced with glycine in equal amounts, while all other conditions remained the same.
[0116] Comparative Example 2
[0117] Example 1 was repeated, except that the 6 parts of modified carbon nanotubes used in the preparation of the carbon nanotube conductive slurry were replaced with the unmodified carbon nanotube powder (average tube diameter of 5-10 nm and average tube length of 30 μm), and all other conditions remained the same.
[0118] Comparative Example 3
[0119] Example 1 was repeated, except that the 6 parts of modified carbon nanotubes used in preparing the carbon nanotube conductive slurry were replaced with 4 parts of unmodified carbon nanotube powder (average tube diameter of 5-10 nm and average tube length of 30 μm) and 2 parts of water, while the other conditions remained the same.
[0120] Comparative Example 4
[0121] Example 4 was repeated, except that 2.5 parts of the modifier 4-amino-1-naphthalenesulfonic acid used in the preparation of modified carbon nanotubes were replaced with an equal amount of aminosulfonic acid, while all other conditions remained the same.
[0122] Comparative Example 5
[0123] Example 4 was repeated, except that the 10 parts of modified carbon nanotubes used in the preparation of the carbon nanotube conductive slurry were replaced with the unmodified carbon nanotube powder (average tube diameter of 20-30 nm and average tube length of 50 μm), and all other conditions remained the same.
[0124] Comparative Example 6
[0125] Example 4 was repeated, except that the 10 parts of modified carbon nanotubes used in the preparation of the carbon nanotube conductive paste were replaced with 8 parts of unmodified carbon nanotube powder (average tube diameter of 20-30 nm and average tube length of 50 μm) and 2 parts of NMP, while the other conditions remained the same.
[0126] The carbon nanotube conductive pastes obtained in Examples 1-4 and Comparative Examples 1-6 were subjected to thermal storage tests. Specific test items included the in-tank state, fineness, and viscosity of the conductive paste. The in-tank state was determined by visual observation; the fineness test method followed national standard GB 1724-79; and the viscosity test method followed national standard GB / T 9268-2008. The specific thermal storage procedure was as follows: the samples were placed in an oven at 50℃±2℃ for 28 days, then removed and stored at 23℃±2℃ for 6 hours. The results of the thermal storage tests on the carbon nanotube conductive pastes obtained in Examples 1-4 and Comparative Examples 1-6 are shown in Table 1.
[0127] Table 1. Thermal storage stability test results of carbon nanotube conductive pastes obtained in Examples 1-4 and Comparative Examples 1-6.
[0128]
[0129]
[0130] As shown in Table 1, the carbon nanotube conductive slurries obtained in Examples 1-4 have low initial viscosity, good dispersibility and flowability. After being stored at 50°C for 28 days, their flowability, fineness, and viscosity remained essentially unchanged, demonstrating extremely high thermal stability. In contrast, the carbon nanotube conductive slurries obtained in Comparative Examples 1-2 and 4-5 have high initial viscosity, poor dispersibility and flowability. After being stored at 50°C for 28 days, their fineness significantly increased, and their viscosity also rose sharply. This is mainly due to the inappropriate selection of modifiers in the carbon nanotube modification process, or the lack of surface modification treatment for carbon nanotubes, which leads to poor wetting and dispersibility of carbon nanotubes. Consequently, the resulting conductive slurries have high initial viscosity, poor flowability, and decreased thermal stability. In Comparative Examples 3 and 6, the content of unmodified carbon nanotubes was further reduced. Although the carbon nanotubes could be dispersed, the fluidity also deteriorated after being stored at 50°C for 28 days. At the same time, the fineness became coarser and the viscosity increased significantly. This further illustrates that the carbon nanotube modification process is helpful in improving the carbon nanotube content, dispersibility, fluidity and storage stability of conductive pastes.
[0131] XPS elemental analysis was performed on the modified carbon nanotubes in Example 4 and Comparative Example 4 to characterize the content of sulfonic acid groups on the surface of the two modified carbon nanotubes. The results are shown in Table 2. It can be seen that when aminosulfonic acid was used instead of 4-amino-1-naphthalenesulfonic acid as the modifier, no sulfur element was detected on the surface of the carbon nanotubes, indicating that the sulfonation modification failed and the sulfonic acid groups were not grafted onto the surface of the carbon nanotubes. This demonstrates the necessity of phenyl or naphthyl groups in the modifier structure.
[0132] Table 2 shows the sulfur content of the modified carbon nanotubes in Example 4 and Comparative Example 4.
[0133] Types of modifiers 4-Amino-1-naphthalenesulfonic acid Aminosulfonic acid S element content 0.84% Not detected
[0134] In summary, this invention discloses an easily dispersible and storage-stable carbon nanotube conductive slurry and its preparation method. The formulation utilizes carbon nanotubes with carboxyl and sulfonic acid groups on their surface after chemical grafting surface treatment. The modification process does not involve concentrated acid treatment, offering advantages such as simple reaction process, mild reaction conditions, and environmental friendliness. The modified carbon nanotubes exhibit excellent dispersion stability in solvents. The prepared conductive slurry features high carbon nanotube concentration, good dispersibility and flowability, and does not settle, separate, or thicken during storage, making it suitable for use as a positive and negative electrode slurry in lithium-ion secondary batteries.
[0135] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing modified carbon nanotubes, characterized in that, The modified carbon nanotubes are carbon nanotubes with carboxylic acid or sulfonic acid functional groups on their surface after surface modification, and their preparation method is as follows: Carbon nanotube powder, modifier and water are mixed to obtain carbon nanotube mixture A; Heating to 65-75℃ and adding an aqueous solution of sodium nitrite yields carbon nanotube mixture B; Add dilute hydrochloric acid to carbon nanotube mixture B to adjust the pH to 1-2, stir at 65-75℃ for 1-2 hours, filter, wash with hot water at 50-60℃ until the pH of the filtrate is 7-8, and collect the filtrate to obtain the final product. The modifier contains at least the following three types of functional groups in its molecular structure: 1) primary amino group; 2) phenyl and / or naphthyl group; 3) carboxyl group; The modifier is selected from one or more of 4-amino-1-naphthoic acid, 5-amino-1-naphthoic acid, p-aminobenzoic acid, and m-aminobenzoic acid; The mass ratio of the carbon nanotube powder, modifier, and water is 10:0.5-4:150-250.
2. The preparation method according to claim 1, characterized in that, The mass ratio of the carbon nanotube powder, modifier, and water is 10:1 to 3:
200.
3. The preparation method according to claim 1, characterized in that, The carbon nanotube powder is selected from one or more of single-walled carbon nanotubes, oligo-walled carbon nanotubes, and multi-walled carbon nanotubes, with an average diameter ranging from 2 to 80 nm.
4. The preparation method according to claim 1, characterized in that, The average diameter of the carbon nanotube powder ranges from 5 to 30 nm.
5. The preparation method according to claim 1, characterized in that, The mass ratio of the carbon nanotube powder to the sodium nitrite aqueous solution is 10:30-50; the concentration of the sodium nitrite aqueous solution is 2-3 wt%.
6. A modified carbon nanotube, characterized in that, It is prepared by the preparation method described in any one of claims 1-5.
7. A carbon nanotube conductive paste, characterized in that, It contains the following raw materials by weight percentage: 0.5-15 wt% of the modified carbon nanotubes as described in claim 6 Dispersant 0.1-15 wt%; The remainder is solvent.
8. The carbon nanotube conductive paste according to claim 7, characterized in that, The dispersant is selected from one or more of the following: styrene / acrylic acid copolymer, polyurethane polymer, polyester polymer, butadiene / acrylic acid copolymer, styrene / maleic acid copolymer, polyethylene glycol monovinyl ether / maleic acid copolymer, polyacrylate or its modified polymer, epoxy polyether amine addition polymer, polyvinylpyrrolidone or its modified polymer.
9. The carbon nanotube conductive paste according to claim 7, characterized in that, The solvent is selected from one or more of water, N-methylpyrrolidone, propylene glycol methyl ether acetate, butyl acetate, and methyl isobutyl ketone.
10. The carbon nanotube conductive paste according to claim 7, characterized in that, The carbon nanotube conductive paste contains 6-12 wt% modified carbon nanotubes.
11. The method for preparing the carbon nanotube conductive paste according to any one of claims 7-10, characterized in that, Includes the following steps: (1) Add the dispersant to the solvent according to the formula amount, and stir at a speed of 800-1000 r / min for 10-20 min to obtain mixture A; (2) Add modified carbon nanotubes to mixture A and disperse them at a high speed of 1500-2000 r / min for 10-20 min to obtain mixture B; (3) Grind mixture B in a sand mill, maintaining the grinding state until the fineness of the material is dispersed to <20μm, to obtain mixture C; (4) The mixture C is subjected to high pressure homogenization dispersion treatment to obtain the carbon nanotube conductive slurry.
Citation Information
Patent Citations
Carbon nanotube dispersant and preparation method thereof
CN108059151A
Preparation method of high-dispersity carbon nanotube, prepared high-dispersity carbon nanotube, conductive slurry and preparation method of conductive slurry
CN113562725A
Preparation method of high-dispersion carbon nanotube conductive liquid
CN116873903A
High -efficient double screw extruder is used in carbon nanotube production
CN206011683U
Surface-modified carbon material, and conductive composition, conductive layer and thermoelectric conversion element which are arranged by use thereof
JP2020205396A